The Effect of Urea Fertilizer Dosage on Growth and Results of Two Types Basil (Ocimum americanum L.). - Prismawan, Nofa; Iriany, Aniek; Sufianto (Universitas Muhammadiyah Malang, 2022)
Basil can be grown in all regions of Indonesia. The purpose of this study was to identify the response of 2 types of basil against the use of N fertilizer dose on the early growth. In the growth process, plants require sufficient nutrients so that the physiological processes in plants’ organs can be held properly. The nutrients used by plants can be sourced from within the soil itself or in the form of fertilizers that have been put into the soil. Plants will grow properly if the elements needed by plants are fulfilled. The research was carried out from February to April 2022 at the Experimental Field of the Faculty of Agriculture and Animal Husbandry at the University of Muhammadiyah Malang. The design used in this study was the factorial Randomized Complete Block Design (RCBD) with a treatment dose of Urea fertilizer in basil type. The results showed that there was no interaction between the types of basil and the dose of urea at all the observation parameters. On the other side, the type of basil affects the parameters of the number of leaves, plant height, and total fresh weight where the type of tidore basil was better than other types of basil. Furthermore, the urea fertilizer dose treatment affected the number of leaves, plant height, and total fresh weight where the better urea fertilizer dose was N125.